Modeling and Seismic Performance Analysis of Grid Shear Walls - Weijing Zhang; Caiwang Li; Xiao Chu (Buildings)
Prefabricated insulation grid shear walls are a new type of wall which integrates structure, insulation and formwork. A grid-like reinforced concrete shear wall with vertical and transverse limbs is formed by casting concrete into the reserved vertical and transverse hollow cavities in the prefabrication of cement polystyrene granular concrete wall formworks. In this paper, based on an earthquake engineering simulation open system (OpenSees), a new modeling approach for grid shear walls is proposed, and nonlinear analysis of two grid walls with different grid sizes under cyclic load is carried out. The accuracy and effectiveness of the grid shear wall model are verified by comparison of the predicted hysteretic response and experimental results. On this basis, the seismic performance of grid shear walls with different parameters (axial load ratio, vertical reinforcement ratio, transverse reinforcement ratio and transverse limb height) is analyzed. The results show that both axial load ratio and vertical reinforcement ratio can significantly improve the load capacity of grid shear walls. However, with an increase in the axial load ratio, the ductility of the grid shear walls decreases. The influence of transverse reinforcement ratio and transverse limb height on the load capacity of shear wall with large shear span ratio is relatively small, mainly because the failure mode of shear wall with large shear span ratio is bending failure. Based on parameter influence analysis, design suggestions for reinforcement ratio in vertical and horizontal limbs and the height of the transverse limb of grid shear walls are put forward. The research in this paper provides a reference for the application of grid shear walls in engineering.